The Effect of Strict Volume Control on Cognitive Functions in Chronic Hemodialysis Patients - Dogukan, Ayhan; Guler, Murat; Yavuzkir, Mustafa Ferzeyn; Tekatas, Arslan; Poyrazoglu, Orhan Kursat; Aygen, Bilge; Yoldas, Tahir Kurtulus (Informa Healthcare, 2009)
Cognitive dysfunction is a well-known complication of chronic renal failure that is evident in 30% of hemodialysis (HD) patients. However, the pathogenesis of this dysfunction is unknown. Left ventricular hypertrophy could develop in hypertensive HD patients without establishing normovolemia. Our aim was to evaluate the effect of strict volume control by salt restriction and ultrafiltration on cognitive functions in HD patients. This cross-sectional study was composed of 22 HD patients who were normotensive by applying a strict volume control, 24 HD patients who were normotensive by receiving anti-hypertensive drugs, and 20 healthy controls. The strict volume control was defined as managing of blood pressure control by strict salt restriction and insistent ultrafiltration. P300 recording as an indicator of cognitive disfunction was measured when blood pressures were reached at target level at the end of six-month follow-up period. In all patients, dimensions of the heart were evaluated with echocardiography on an interdialytic day. The cardiothoracic ratio and echocardiographic dimensions were significantly lower in patients with strict volume control. P300 amplitudes were significantly lower in patients on antihypertensive drugs than in patients with strict volume control (9.5 +/- 5.1 versus 11.3 +/- 5.4 mu V). P300 latency was longer in patients on antihypertensive drugs than in the control group and patients with strict volume control (359.9 +/- 39.6 versus 345.6 +/- 36.7 ms). Our results suggest that hypervolemia may be one of the causal and potentially modifiable factors of cognitive dysfunction. Strict volume control may have beneficial effects on cognitive functions in hemodialysis patients.
Keywords: hemodialysis; strict volume control; echocardiography; left ventricular hypertrophy; cognitive function